PENERAPAN PERATURAN MENTERI PEKERJAAN UMUM DAN PERUMAHAN RAKYAT NOMOR 11/PRT/M/2019 TENTANG SISTEM PERJANJIAN PENDAHULUAN JUAL BELI RUMAH - Khairunnisah dan Wesley Liano Hutasoit (Universitas 17 Agustus 1945 Samarinda, 2020)
During its development, a house sale and purchase agreement made by the parties by a notary public creates rights and obligations as well as risks for the parties later. Before the agreement is agreed upon, the parties express their wishes or wishes so that the objectives of the house sale and purchase agreement are achieved, so that when the agreement is implemented, all of these rights and obligations must be fulfilled by the parties to fulfill each other's wishes. The House Sale and Purchase Agreement when viewed from the latest legal rules, namely, the Regulation of the Minister of Public Works and Public Housing (PUPR) of the Republic of Indonesia, issued a Ministerial Regulation (Permen) PUPR Number 11 / PRT / M / 2019 concerning the Preliminary House Buying Agreement System. This regulation was signed by the Minister of PUPR, M. Basuki Hadimuljono, on July 12, 2019. This regulation regulates the sale of houses or flats by developers to the community. The issues raised in this paper are how the legal protection for home buyers is based on the Ministerial Regulation (Permen) PUPR Number 11 / PRT / M / 2019 and what are the legal requirements that home developers must have in selling their products based on Ministerial Regulation (Permen) PUPR Number 11 / PRT / M / 2019. The type of research used is juridical normative, which is research conducted based on legal materials and by collecting data, studying books in the library and the laws and regulations related to this research. The results of research by developers or housing developers that are legal entities who sell single houses, row houses and flats that are sold to the community by means of cash or credit, in terms of credit, there are many problems caused in terms of payments, broken promises, and inadequacy of development.